2010
DOI: 10.1111/j.1476-5381.2009.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic sympatho‐inhibition on reflex control of renal blood flow and plasma renin activity in renovascular hypertension

Abstract: Background and purpose:We determined if chronic sympatho-inhibition with rilmenidine has functional significance for the kidney by altering responses of renal blood flow (RBF) and plasma renin activity (PRA) to stress and acute hypotension in rabbits with renovascular hypertension. Experimental approach: RBF to each kidney and renal sympathetic nerve activity (RSNA) to the left kidney were measured in rabbits in which a renal artery clip induced hypertension (2K1C) and in sham-operated rabbits. After 2 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…3,4,7,16 Blocking the RAAS by inhibiting renin with ALSK could therefore contribute to reducing renovascular hypertension in the rat model we studied. However, we found that ALSK monotherapy did not reduce SBP, while studies in humans have demonstrated a reduction of blood pressure.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…3,4,7,16 Blocking the RAAS by inhibiting renin with ALSK could therefore contribute to reducing renovascular hypertension in the rat model we studied. However, we found that ALSK monotherapy did not reduce SBP, while studies in humans have demonstrated a reduction of blood pressure.…”
Section: Discussionmentioning
confidence: 98%
“…10 Renal nerves are known to produce renal vasoconstriction, albeit at higher levels of RSNA than are required to release renin. 4 Importantly, in the two-kidney, one-clip (2K1C) model of renovascular hypertension, excitatory synaptic inputs to the rostral ventrolateral medulla and the cardiac sympathetic afferent reflex are enhanced, 10 factors that may partly contribute to sympathetic activation and hypertension. 11 In 2K1C renovascular hypertension, the renal artery stenosis caused by the clip reduces the perfusion of the clipped kidney, raising plasma renin activity and circulating angiotensin II (Ang II), and increasing systolic blood pressure (SBP).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations